Aksesibilitas Modal Penghidupan Rumah Tangga Peternak Domba di Kecamatan Wanaraja Kabupaten Garut - Suhendarsyah, Suhendarsyah; Yunasaf, Unang; Kuswaryan, Sondi (Universitas Galuh, 2026)
This study investigates the accessibility of livelihood capital among sheep-farming households in Wanaraja District, Garut Regency, Indonesia. A quantitative research design was applied through a structured survey involving 95 sheep farmers. Livelihood capital accessibility was conceptualized across five dimensions: human, natural, financial, social, and physical capital. Data were analyzed using the Entropy Weight Method to objectively determine the relative contribution of each dimension in shaping overall livelihood capital accessibility. The results indicate that financial capital is the most accessible dimension among sheep farmers, highlighting the dominant role of financial resources in supporting their livelihood strategies. In contrast, human, social, physical, and natural capital remain less accessible, suggesting that these dimensions have not been fully optimized to enhance the resilience and sustainability of rural livelihoods. These findings underscore the importance of strengthening non-financial forms of capital to achieve a more balanced and sustainable livelihood system among smallholder livestock farmers.